2012
DOI: 10.1371/journal.pone.0038396
|View full text |Cite
|
Sign up to set email alerts
|

Red Sea Coral Reef Trajectories over 2 Decades Suggest Increasing Community Homogenization and Decline in Coral Size

Abstract: Three independent line intercept transect surveys on northern Red Sea reef slopes conducted in 1988/9 and 1997/8 in Egypt and from 2006–9 in Saudi Arabia were used to compare community patterns and coral size. Coral communities showed scale-dependent variability, highest at fine spatial and taxonomic scale (species-specific within and among reef patterns). At coarser scale (generic pattern across regions), patterns were more uniform (regionally consistent generic dominance on differently exposed reef slopes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 25 publications
7
77
2
Order By: Relevance
“…The seas surrounding the Arabian Peninsula, including the Red Sea (RS), the Sea of Oman (SO), and the Persian/Arabian Gulf (PAG), represent an understudied marine region despite hosting a large diversity of coral reef ecosystems (Riegl et al ., 2012; Bauman et al ., 2013; Coles et al ., 2015). The RS is an oligotrophic system with high temperature variation and high salinity due to low influx of freshwater, high evaporation and limited exchange with the Indian Ocean (Sheppard et al ., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The seas surrounding the Arabian Peninsula, including the Red Sea (RS), the Sea of Oman (SO), and the Persian/Arabian Gulf (PAG), represent an understudied marine region despite hosting a large diversity of coral reef ecosystems (Riegl et al ., 2012; Bauman et al ., 2013; Coles et al ., 2015). The RS is an oligotrophic system with high temperature variation and high salinity due to low influx of freshwater, high evaporation and limited exchange with the Indian Ocean (Sheppard et al ., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This observation agrees with that of Attalla (2011), who studied the effect of the sheltering condition on the substrate composition at the northern Red Sea and found similar pattern. In addition, the results from the reef assessments in the Red Sea over two decades 1988-1997 on the Egyptian reefs suggest a little change in community structures with the temporal change (Riegl et al, 2012). The total living cover in all sites did not affected with the occurred human impact such as coastal development, diving activities and some fishing activities.…”
Section: Discussionmentioning
confidence: 86%
“…Kaufman and Tschirky, 2010;Obura and Mangubhai, 2011;Kaufman et al, 2011;ICRI, 2012;Jackson et al, 2014). The losses of marine habitats are the highest in coastal areas largely as a result of conflicting uses of coastal habitats due to the coastal development which increased in last two decade Southern Red Sea and these by turn effects on the diversity of species in the some reefs and the variation between them in the tolerance and stress (Riegl et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although, the Red Sea is at the most northwestern end of the tropical Indo-Pacific, coral diversity is high (>260 hermatypic coral species) and reef communities are complex throughout the Red Sea [5]. While a thorough study on coral community structure and diversity patterns in 1991 identified a clear zonation into a northern, central and southern Red Sea region a [6] recent study on coral communities suggested an increase in community homogenization within the last two decades throughout the Red Sea [7]. This was inter alia related to environmental changes such as ocean warming [7], which affects some species more than others [8], leading to a decimation of some species and a spread of other pecies [7].…”
Section: Introductionmentioning
confidence: 99%
“…While a thorough study on coral community structure and diversity patterns in 1991 identified a clear zonation into a northern, central and southern Red Sea region a [6] recent study on coral communities suggested an increase in community homogenization within the last two decades throughout the Red Sea [7]. This was inter alia related to environmental changes such as ocean warming [7], which affects some species more than others [8], leading to a decimation of some species and a spread of other pecies [7]. However, it remains to be assessed whether changes in coral abundance and diversity patterns in the Red Sea alter the reef functionality and whether differences in the functionality (ecological role) exist along the latitudinal gradient.…”
Section: Introductionmentioning
confidence: 99%